2021
DOI: 10.1080/21645515.2021.1930471
|View full text |Cite
|
Sign up to set email alerts
|

A case control study to assess effectiveness of measles containing vaccines in preventing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children

Abstract: Currently, most licensed vaccines against SARS-CoV-2 infection are approved for adults and not for children. We conducted a test negative case-control study to assess the effectiveness of Measles Containing Vaccines (MCVs) against SARS-CoV-2 infection in Pune, India, in children who were ≥1 year and <18 years of age and were tested for SARS-CoV-2 infection by Reverse transcription polymerase chain reaction (RT-PCR). The enrolled participants included 274 SARS-CoV-2 positive cases (216 vaccinated and 58 unvacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This may have impacted the antibody titres, potentially resulting in a false lack of association. In terms of disease severity, the current study is consistent with a previous study by Gujar et al, which reported fewer symptomatic cases in the MR-vaccinated group compared to the unvaccinated group [ 16 ]. However, the current study may have been limited by the recruitment of mostly asymptomatic and mild cases, and further studies with larger sample sizes and longer follow-up periods are needed.…”
Section: Discussionsupporting
confidence: 92%
“…This may have impacted the antibody titres, potentially resulting in a false lack of association. In terms of disease severity, the current study is consistent with a previous study by Gujar et al, which reported fewer symptomatic cases in the MR-vaccinated group compared to the unvaccinated group [ 16 ]. However, the current study may have been limited by the recruitment of mostly asymptomatic and mild cases, and further studies with larger sample sizes and longer follow-up periods are needed.…”
Section: Discussionsupporting
confidence: 92%
“…76 A case-control study in children also showed that children vaccinated with a measles-containing vaccine had lower infection rates with SARS-CoV-2 and, if infected, had milder symptoms. 77 Another study found that the outcome of COVID-19 inversely correlated with levels of rubella-specific antibodies 70 and another with levels of mumps-specific antibodies. 78 An interim analysis of an ongoing randomized control trial (RCT) of MMR to reduce SARS-CoV-2 infection and severity in health care workers reported that MMR reduces the risk of symptomatic infection.…”
Section: Mechanisms Which Are More Likely To Contribute To the Age-re...mentioning
confidence: 99%
“…5 In December 2019 the community was excited about the occurrence of the COVID-19 disease. 6 World The Health Organization declared COVID-19 on March 12, 2020 as a pandemic. 7 And on March 2, 2020, the first 2 cases of COVID-19 infection were found which were reported by President Joko Widodo.…”
Section: Introductionmentioning
confidence: 99%